Critical Criminology, Traditional Crime, and Public Policy - Kramer, Ronald C. (1984)
Critical criminologists have often ignored the serious problem of traditional or common street crime. As a result, crime prevention policy has been forfeited to the political right or to those who advocate ineffective liberal reforms. This paper argues that critical criminology can make a contribution to the formulation of public policy concerning traditional crime. Recent theoretical developments within the criitical perspective on crime, as.well as a variety of supporting data, are reviewed and specific policy recommendations to reduce traditional crime are offered. These progressive recommendations constitute an important alternative to the individualistic approaches (liberal or conservative) which now dominate crime prevention policy